REVITALIZING SUMITRO DJOJOHADIKUSUMO'S ECONOMIC LEGACY: PATHWAYS TO INDONESIA'S ECONOMIC SELF-RELIANCE IN THE DIGITAL AND GLOBALIZATION ERA - Muhammad Said; Syahriyah Semaun; Ahmad Dzul Ilmi Syarifuddin; Minhajuddin Madi; M. Rafly Al Farezy Arif (JURNAL PROFIT, 2025)
This study aims to develop a conceptual framework for revitalizing the economic thought of Prof. Dr. Sumitro Djojohadikusumo as a strategic roadmap toward Indonesia’s economic sovereignty in the digital and globalization era. Using a qualitative approach based on library research, this study systematically examines primary and secondary literature on Sumitro’s thought, development theory, and contemporary digital economic dynamics through content analysis. The findings introduce the concept of “Digital Economic Nationalism” as an adaptation of Sumitro’s development trilogy economic growth, national stability, and equitable development into the digital context, operationalized through the “Digital Gotong Royong Economy” model. This model integrates rural digital infrastructure, local economic platforms, digital cooperatives, sustainable financing, and the protection of national economic value. The results demonstrate that Sumitro’s intellectual legacy remains relevant and offers a theoretical and practical alternative to the dominant neoliberal model in the digital economy, while opening new avenues for nationally grounded digital political economy studies.